2013
DOI: 10.1038/nature12357
|View full text |Cite
|
Sign up to set email alerts
|

Structure of class B GPCR corticotropin-releasing factor receptor 1

Abstract: Structural analysis of class B G-protein-coupled receptors (GPCRs), cell-surface proteins that respond to peptide hormones, has been restricted to the amino-terminal extracellular domain, thus providing little understanding of the membrane-spanning signal transduction domain. The corticotropin-releasing factor receptor type 1 is a class B receptor which mediates the response to stress and has been considered a drug target for depression and anxiety. Here we report the crystal structure of the transmembrane dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
463
0
16

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(493 citation statements)
references
References 53 publications
14
463
0
16
Order By: Relevance
“…3a–b). This α-helical extension elevates the position of ECL1, which is ordered against the C-terminal half of the peptide, in contrast to its apparent disorder in all available family B GPCR structures 810 . Consistent with this observation, hydrogen/deuterium exchange studies and MD simulations also indicate the peptide binding event stabilizes the conformation of ECL1 in the glucagon-GCGR complex 32 .…”
Section: Comparison With Inactive Family B Receptorsmentioning
confidence: 93%
See 2 more Smart Citations
“…3a–b). This α-helical extension elevates the position of ECL1, which is ordered against the C-terminal half of the peptide, in contrast to its apparent disorder in all available family B GPCR structures 810 . Consistent with this observation, hydrogen/deuterium exchange studies and MD simulations also indicate the peptide binding event stabilizes the conformation of ECL1 in the glucagon-GCGR complex 32 .…”
Section: Comparison With Inactive Family B Receptorsmentioning
confidence: 93%
“…In the active GLP-1R complex, the extracellular half of TM6 unwinds and moves outwards to allow interactions between the peptide amino terminus and the TMD binding pocket. The extracellular half of TM1 follows the movement of TM7, dictated by the hydrogen bond between highly conserved S155 1.50b and the backbone of L396 7.51b , which was found to stabilize the kink in TM7 in both apo and inactive family B GPCRs 810 . In addition, more limited changes are observed in the extracellular halves of TM3, TM4, and TM5, which appear to move in tandem with the same orientation in response to peptide binding (Fig.…”
Section: Comparison With Inactive Family B Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that tertiary interactions between the ECD and TMD play a critical role in regulating receptor activity of class B GPCRs 6,7 . Structures of the ECDs of several class B GPCRs have been solved 2 , and recently, the crystal structures of the TMDs of three class B GPCRs, the human GCGR 8,9 , corticotrophin-releasing factor receptor 1 (CRF 1 R) 10 and glucagon-like peptide-1 receptor (GLP-1R) 11 , have been determined, providing insights into ligand recognition and selectivity of these physiologically important receptors. However, the structure of a full-length class B GPCR has remained elusive, thereby limiting our understanding of the molecular details accompanying peptide binding and signal transduction.…”
mentioning
confidence: 99%
“…Perhaps more important than the total number of structures being solved are the number of truly challenging projects being undertaken there. In addition to the outstanding examples in the accompanying articles in this volume, there are many others, including large macromolecular complexes [21,22], membrane proteins [23][24][25][26] and virus structures [16,27].…”
mentioning
confidence: 99%